Advanced Heart Block During Acute Myocardial Infarction Treated with an Electrode Pacing Catheter - Peretz, Dwight I. (1967)
The mortality rate is high from advanced atrioventricular block associated with acute myocardial infarction. There is reason to believe that if in these patients the hearts are electrically paced with an endocardial pacing catheter, the mortality rate can be considerably decreased. Five patients in second- and third-degree heart block associated with acute myocardial infarction were paced with a considerable lowering of the expected mortality rate. Twenty-three cases from the literature are also presented and discussed. A silastic bipolar electrode catheter was used in these five cases. Four of the five cases returned to normal sinus rhythm within the first 10 days. The average duration of pacing was 6.7 days. It is the opinion of the author that second- and third-degree heart block associated with acute myocardial infarction should have a pacing catheter introduced at the earliest possible moment for continuous or demand endocardial pacing.